O processo estratégico de marketing em pequenas e médias empresas de desenvolvimento de software: um estudo de casos múltiplos - Gomes, Victor Márcio Laus Reis (Universidade do Vale do Rio do Sinos, 2008)
This dissertation is focused on the strategic marketing process, which involves the formulation and the implementation of marketing strategies, in small and medium software development companies. Its objectives are to analyze the process, examining the relation between formulation and implementation and the role of improvisation and adaptation on the strategic marketing process. It also investigates the executives of the analyzed companies’ perception of the strategic marketing process contribution to the creation of competitive advantage, as well as the representation of the strategic marketing content in promotional materials. A multiple-case study was conducted in five software development companies, four small companies and one medium. The evidences were collected through semi-structured interviews and promotional materials. The cases were first individually analyzed and then a comparative analysis was conducted. The integration between formulation and implementation was identified, as well as the influe
Keywords: gestão de marketing; processos estratégicos; estratégia de marketing; marketing management; strategic marketing process; marketing strategy; Ciências Sociais Aplicadas